INSECTICIDES USED TO CONTROL FRUIT FLIES IN THE APPLE ORCHARDS: ACTION ON Neoseiulus californicus (ACARI: PHYTOSEIIDAE) - MONTEIRO, Lino Bittencourt (Scientia Agraria, 2001)
The objective of this work was to evaluate the effect of insecticides malathion, azinphos ethyl, phosmet and fenthion about two populations of Neoseiulus californicus (McGregor). The first population was reared in the tray (PCB) and not recevied any inseticide during two year and the second population was released in the orchard (PLP) and its development was influenced to the insecticides for the control of Anastrepha fraterculus (Wied). Twenty four females of both populations of known ages was reared inside of twelve cells of 2x2 cm and were fed females of Tetranychus urticae (Koch). The insecticides were sprayed with a Desaga atomizer, nº 124000 (Heidelberg) that spreaded a fine and homogeneous spraying. Assessment of oviposition and death was done after 12, 24, 72 and 96 hours. Phosmet and malathion killed 50% and 66% of N. californicus of PLP and PCB, respectively in the advisable concentration for apple, while was observation with fenthion and azinphos ethyl in the 1.500 ppm concentration were very toxic, and ovoposition did not ocurr on both populations. The conclusion was that the PLP under insecticide pressure was more tolerant to phosmet and malathion than PCB, under apple orchad conditions during five months.